2019
DOI: 10.1039/c9ta03001h
|View full text |Cite
|
Sign up to set email alerts
|

An air-stable electrochromic conjugated microporous polymer as an emerging electrode material for hybrid energy storage systems

Abstract: An air-stable oxidation state is observed in an electrochromic triphenylamine–triazine polymer energy storage system after the removal of the applied potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 109 publications
(51 citation statements)
references
References 60 publications
1
50
0
Order By: Relevance
“…In some previous studies, because of the lack of accurate structural information, monomeric units have been approximated to completely planar, “star‐shaped” building blocks . As a result, it has been assumed that the highly porous polymers observed result from the aggregation of monomers into cyclic units which build together into planar, honeycomb arrangements, for example, in poly[1,3,5‐tris(4‐diphenylamino‐phenyl)benzene], which has been shown to possess a highly porous structure.…”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…In some previous studies, because of the lack of accurate structural information, monomeric units have been approximated to completely planar, “star‐shaped” building blocks . As a result, it has been assumed that the highly porous polymers observed result from the aggregation of monomers into cyclic units which build together into planar, honeycomb arrangements, for example, in poly[1,3,5‐tris(4‐diphenylamino‐phenyl)benzene], which has been shown to possess a highly porous structure.…”
Section: Resultsmentioning
confidence: 94%
“…In some previouss tudies, because of the lack of accurate structurali nformation,m onomeric units have been approximated to completely planar," star-shaped" building blocks. [19,23] As ar esult,i th as been assumed that the highly porous polymers observed result from the aggregationo fm onomers into cyclic units which build together into planar,h oneycomba rrangements, for example, in poly[1,3,5-tris(4-diphenylaminophenyl)benzene],w hich has been shown to possess ah ighly porouss tructure. However,t he TEPAm onomer is not ac ompletely planarb uildingb lock but is slightly pyramidalized at the central N1 atom with respectt ot he terminal Ca toms (C1A, C1B, C1C), whichf orm CÀCb onds to other monomer units upon polymerization (Figure 5a).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ED method was a "one-step" preparation process combining polymerization and in situ deposition on destination electrodes to afford an insoluble and infusible film with high cross-linking degree. [36][37][38][39] Experimental results showed that the cross-linked azobenzene film exhibited smooth morphology without obvious crack and aggregation, and expected photoresponse, which could be applied to ready-to-used STF. Moreover, due to the suppressed molecular motion in crosslinked structure, the ED azobenzene film realized significantly improved energy storage half-life, which was extended by 750% compared with that of BCz-BO-Azo solid.…”
mentioning
confidence: 99%